Improving the welfare of the Amur leopards (Panthera pardus orientalis) at Nordens Ark (Sweden) - Slof Pacilio, María (2020)
Since recent years, people do not only want to prevent animal cruelty anymore, but also want to improve their welfare. Therefore, zoo institutions are under pressure to assure the wellbeing of their animals. And even though they work very hard to achieve this, it is not an easy job. Carnivores, most notably solitary felids, are amongst the most difficult species for whom to develop a proper environment. Previous studies conducted on the two Amur leopards currently living at Nordens Ark recorded signs of stress and pacing. However, no previous individual assessment had been carried out to evaluate their welfare and find out the possible reasons behind their behavior. The aim of this study was (1) to evaluate and improve the welfare of the two Amur leopards currently living at Nordens Ark, and (2) to find out if making changes in their environment could be a way to improve their welfare. To this end, a behavioral study was carried out during different periods of time on both individuals, while being exposed to four changes in their environment concerning training, increased zookeeper presence, increased environmental enrichment and visual barriers. Overall, these changes seem to have had a positive effect on both leopards. However, they still showed signs of poor welfare and more effort needs to be put to ensure their best welfare quality. Emphasis has been given to provide varying enrichment and training, and increasing presence of keepers. Moreover, individual differences due to different personalities should be taken into consideration.